(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article presents data on the influence of environmental factors on the generative development stages of winter wheat in the agrocenoses of the Khorezm region, Republic of Uzbekistan. The study primarily analyzes the impact of ecological factors particularly temperature on the biological and physiological condition of winter wheat, as well as the crop’s adaptation processes to climatic conditions. The analysis of these data significantly contributes to understanding the ecological potential of winter wheat agrocenoses under the conditions of the Khorezm region. Furthermore, the results of the study provide a scientific basis for increasing future crop yields of winter wheat and offer practical recommendations for agronomists, farmers, and agricultural specialists. These recommendations aim to enhance productivity based on essential information about climatic factors.